Nematodes of spruce forests at the Lyalsky test area in the European part of Russia (Komi Republic) ... - Kudrin, Alexey (Institute of Biology of Komi Scientific Centre of the Ural Branch of the Russian Academy of Sciences, 2023)
The dataset furnishes information on soil nematodes inhabiting various types of spruce forests situated in the Lyalsky test site of the middle taiga as part of the CARBON RITM project. ...